Status of Rice Diseases in Northern Himalayas: A Case Study of Himachal Pradesh - , Shikha Sharma; , DK Banyal; , Sonali Parwan; , Shiwali Dhiman; , Sachin Upmanyu; , Neelam Bhardwaj; , Anchal Thakur (Archives of Current Research International, 2025)
Rice production around the world is threatened by various diseases leading to biotic stress. Surveys during 2022 & 2023 were conducted in eight districts of Himachal Pradesh to assess the status of rice diseases. Seed health status of farmers saved seed was also monitored. Surveys of the crop revealed the occurrence and incidence of varying degrees of diseases viz., bacterial leaf blight, neck blast, sheath rot, false smut, brown spot, narrow brown spot, rice stunting and leaf scald. Association of mycoflora i.e Ustilaginoidea virens, Pyricularia oryzae and Helminthosporium oryzae in farmer saved seed was also observed. The results of this study can be implemented to curtail the yield losses associated with seed borne diseases and can further improve sustainable rice production in Himachal Pradesh.